PENGARUH MANAJEMEN PENDIDIKAN DAN KINERJA GURU TERHADAP PRESTASI AKADEMIK SISWA DI MAN KOTA BATU - Sari, Erma Yunita; Abidin, Munirul (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the impact of educational management and teacher performance on students' academic achievements. The research employs a quantitative method with a non-experimental approach, involving students and teachers from MAN Kota Batu as respondents. A total of 100 respondents were selected using the proportionate stratified random sampling technique. Data were collected through questionnaires measuring three variables: educational management (X1), teacher performance (X2), and students' academic achievements (Y). The findings of the data analysis revealed the following: 1) Educational management has a positive and significant effect on students' academic achievements at MAN Kota Batu, with a t-value of 37.614 > t-table value of 1.9847, indicating that educational management significantly influences students' academic performance. 2) Teacher performance also shows a positive and significant impact on students' academic achievements at MAN Kota Batu, with a t-value of 16.293 > t-table value of 1.9847, confirming that teacher performance plays a role in enhancing students' academic outcomes. 3)The combined effect of educational management and teacher performance on students' academic achievements is both positive and significant, as evidenced by an F-value of 1658.230 > F-table value of 3. 090.These results suggest that educational management and teacher performance significantly influence students' academic achievements. Therefore, educational institutions can strengthen their management systems by involving all school stakeholders and implementing evaluation systems to monitor teacher performance effectively.